Metode cerita al qur’an dan penerapan dalam konteks arsitektur - Hardiansyah, Nur (Maliki Interdisciplinary Journal, 2025)
This paper discusses the significance of the storytelling method in the Qur’an and its application in architecture. As the primary source of Islamic teachings, the Qur’an contains numerous stories, parables, and metaphors that not only convey religious values but also serve as inspiration for architectural design. This study identifies various examples of stories in the Qur’an, such as the narratives of the prophets, parables, and depictions of heaven and hell, which reflect concepts of justice, simplicity, and harmony with nature. The analysis aims to understand how these values can be integrated into architectural design, particularly in the construction of mosques, Islamic cultural centers, and other public buildings. Additionally, this study highlights architectural projects that have applied Qur’anic storytelling principles as design guidelines. The findings indicate that the storytelling method in the Qur’an is relevant to modern architecture as it helps create environments that reflect Islamic identity while supporting the social and spiritual well-being of society. Through this approach, architecture not only serves as a physical representation but also functions as a medium to enhance understanding of Islamic values in everyday life.